The effectiveness of palm oil liquid waste enriched media on growth of Chlorella sp. in the outdoor scale - Febriana Nur Vitriani; Budijono '; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The liquid waste of palm oil containing high nutrients and can be used as a source of nutrients for growth microalgae such as Chlorella sp. A research aims to understand the effects of palm oil liquid waste addition in the media toward the growth of Chlorella sp. has been conducted from May – July 2016. The culture was conducted for 20 days. There were 4 treatment applied, namely P0 (0% waste), P1 (20% waste), P2 (25% waste) and P3 (30% waste). Parameters measured were the abundance and biomass of Chlorella sp., temperature, pH, nitrate, and phosphate. Result shown that the best growth of Chlorella sp. was in the P1, the abundance was 61.45 × 105 cells/ml and the biomass was 0.36 g/l. During the research, the nutrient available in the media decreased, from 1.13 to 0.09 mg/l (nitrate) and from 3.54 to 0.48 mg/l (phosphate). This fact indicates that the nutrient have been used for growing the microalgae. Based on data obtained, it can be concluded that the palm oil liquid waste can be used as a source of nutrients for Chlorella sp.Key words : Palm oilliquid waste, nutrients, microalgae, Chlorella sp.